Ghosts, ghouls, doubles...“Romantic” transgressions in the novel Podobojí by Daniela Hodrová - Balcerzak, Małgorzata (Poznańskie Studia Slawistyczne, 2011)
This article concentrates on the problem of transgression in the novel Podobojí by Daniela Hodrová. This problem is tracked from the perspective of romantic and post-romantic references to the literary and historical tradition (e.g. the Czech National Revival). One of the key concepts here is death and the metaphor of doubling, which makes the characters in the novel ontologically ambiguous entities. Death is treated in a confrontation with romantic themes, such as the ghost, ghoul, and the double.